Intelligent spherical joints based tri-actuated spatial parallel manipulator for precision applications. (December 2018) - Khalid, Azfar; Mekid, Samir
Highlights: A new tabletop size, tri-actuated, spatial parallel manipulator is designed. The robotic configuration is selected due to its ability to provide maximum achievable workspace freedom. A minimum of three legs with all the spherical joints is selected to make three SPS (Spherical-prismatic-spherical) kinematic chain configuration. The complexity in design of such a manipulator lies in the fact that it does not have stiffness as the moving platform stands on six ball joints. The stiffness in individual ball joints is designed with a suitable pre-load for smooth functioning and an electromagnetic actuation for joint locking at the destination point. The manipulator overall stiffness is then evaluated to make its use in micro-meso scale applications. Abstract: This paper contributes to the design of a new table top size tri-actuated spatial parallel manipulator. The manipulator configuration is considered for its ability to provide a maximum achievable workspace freedom. A minimum of three legs with all the spherical joints is selected to make three SPS (Spherical-prismatic-spherical) kinematic chain configuration. The complexity of building a minimum constraint manipulator lies in the fact that it cannot stand on its own on three ball joints. To transform this into a workable mechanism, spherical joints are designed with internal stiffness and braking system such that the manipulator can withstand even external loads. A detailed design analysis is conducted for the customized ball joint with different inside actuation mechanisms. Manipulator working in the workspace is found smooth under a pre-loaded condition whereas magnetic actuation locks the joints at the destination point, thereby achieving both capabilities. The manipulator overall stiffness is then evaluated to make its use in micro‑meso scale applications.